Anthropology in the financial crisis - Hart, Keith; Ortiz, Horacio (Anthropology Today, 2008)
This editorial considers the opportunities opened up for anthropologists by the financial crisis of 2008. The chief of these is the exposure of cracks in the intellectual hegemony of free-market economics which contributed to an unnecessarily defensive posture on the part of most anthropologists during the period of neoliberal globalization. The authors claim that anthropology can bridge the gap between everyday life and the world at large by combining the study of ideas and social actions. We draw on Ortiz's research among financial professionals to show how working practices informed by economic liberalism can have extremely unequal consequences for the global distribution of resources. The perspectives of Mauss and Polanyi on political economy can help us to make sense of the current situation and to recommend a path forward beyond market fundamentalism. Their general ideas lend power to the concrete findings of field research. The mask of neoliberal ideology has been ripped from the politics of world economy. Anthropology's highest mission is to start from where people are and go with them wherever they take you. What better time to follow this imperative than when the model the world has been compelled to live by for three decades is in such disarray?
Keywords: finance; financial crisis

The Anthropology of Money and Finance: Between Ethnography and World History - Hart, Keith; Ortiz, Horacio (Annual Review of Anthropology, 2014)
We review here recent developments in the anthropology of money and finance, listing its achievements, shortcomings, and prospects, while referring back to the discipline's founders a century ago. We take our departure from the work of Marcel Mauss and Karl Polanyi, both of whom combined openness to ethnographic research with a vision of world history as a whole. Since the 1960s, anthropologists have tended to restrict themselves to niche fields and marginal debates. The anthropological study of money and ethnographies of finance, in particular, have been the focus of much research since the 1980s. Despite taking on new objects and directions, anthropologists still find it difficult to connect their situated analyses with global processes and world history. We propose some conceptual and empirical directions for research that would seek to overcome these limitations by integrating ethnography more closely with human history, while stressing the importance of money in shaping world society and attempts to reform it.
Keywords: MAUSS, Marcel, 1872-1950; distribution; economic anthropology; ethnology; exchange; finance; globalization; history; money; politics; world society